TB and diabetes in Eswatini: Addressing suboptimal treatment outcomes through integrated services. - Yael Hirsch-Moverman; Dana Bezuidenhout; Sakthi Senthilvelan; Lobsang Palmo; Debrah Vambe; Ntombifuthi Ginindza; Nonhlanhla Dlamini; Andrea A Howard; Joanne E Mantell (PLOS Global Public Health, 2025)
Tuberculosis (TB) remains a significant public health challenge in Eswatini, a country with the highest global HIV prevalence. Diabetes mellitus (DM) is increasingly common among people newly diagnosed with TB, contributing to suboptimal TB treatment outcomes, including relapse and death. The DETECT study employed a multi-method approach to assess the prevalence and DM impact on TB treatment outcomes among adults with TB in 10 Ministry of Health facilities in Eswatini, and explore barriers and facilitators to integrating TB/DM services. DM screening was conducted using laboratory-based glycated hemoglobin (A1c) testing, with DM defined as A1c ≥ 6.5% and preDM as A1c 5.7-6.4%. We conducted logistic regression to assess DM's impact on TB treatment outcomes and 40 in-depth interviews with key stakeholders involved with TB services to explore barriers and facilitators to TB/DM service integration. Among the 373 adults diagnosed with TB and tested for DM, 13.4% had DM, 41.8% had preDM, and 44.8% had a normal A1c. The odds of poor TB treatment outcomes were 3.53 times higher (95%CI: 1.72-7.32) among those with DM compared to those without DM, after adjusting for age, HIV status, and new versus previously treated TB, highlighting the need for early DM diagnosis and treatment. Patient education and support, adequate screening resources, and community engagement were identified as facilitators of TB/DM service integration. Barriers included health system financial constraints, a perceived lack of need for exercise, insufficiently trained TB healthcare providers, inadequate supplies, societal stigma, limited patient autonomy in decision-making, and the unaffordability of healthy diets. The study found a high prevalence of DM/preDM among adults with TB in Eswatini, with DM significantly increasing the odds of poor TB treatment outcomes, irrespective of HIV status. The findings underscore the urgent need for enhanced tools and strategies to support healthcare providers in integrating TB and DM services effectively.